The fall of Freddie the leaf : a story of life for all ages - Buscaglia, Leo F. (Thorofare, N.J. : Slack ; New York : distributed by H. Holt, 2002)
As Freddie experiences the changing seasons along with his companion leaves, he learns about the delicate balance between life and death.
Keywords: Leaves -- Juvenile fiction; Seasons -- Juvenile fiction; Life -- Juvenile fiction; Death -- Juvenile fiction; Nature -- Juvenile fiction; Seasons; Life -- Juvenile Literature; Death -- Juvenile Literature; Nature -- Juvenile Literature; Seasons; Life -- Juvenile Literature; Death -- Juvenile Literature; Nature -- Juvenile Literature; Leaves -- Juvenile fiction; Seasons -- Juvenile fiction; Life -- Juvenile fiction; Death -- Juvenile fiction; Nature -- Juvenile fiction; Nature stories